[block](log4(2-x)-log_(14)(2-x))/(log_(14)x-log(49)x) ≤ log4 49[/block]
[m]\left\{\begin {matrix}2-x>0\\x>0\end {matrix}\right.[/m] ⇒ 0 < x <2
Переходим к основанию 4:
[m]\frac{log_{4}(2-x)-\frac{log_{4}(2-x)}{log_{4}14}}{\frac{log_{4}x}{log_{4}14}-\frac{log_{4}x}{log_{4}49}} ≤ log_{4}49[/m]
[m]\frac{log_{4}(2-x)(1-\frac{1}{log_{4}14})}{log_{4}x(\frac{1}{log_{4}14}-\frac{1}{log_{4}49})} ≤ log_{4}49[/m]
[m]1-\frac{1}{log_{4}14}=\frac{log_{4}14-log_{4}4}{log_{4}14}=\frac{log_{4}\frac{14}{4}}{log_{4}14}=\frac{log_{4}\frac{7}{2}}{log_{4}14}[/m]
[m]\frac{1}{log_{4}14}-\frac{1}{log_{4}49}=\frac{log_{4}49-log_{4}14}{log_{4}14\cdot log_{4}49}=\frac{log_{4}\frac{49}{14}}{log_{4}14\cdot log_{4}49}=\frac{log_{4}\frac{7}{2}}{log_{4}14\cdot log_{4}49}[/m]
[m]\frac{log_{4}(2-x)\cdot \frac{log_{4}\frac{7}{2}}{log_{4}14}}{log_{4}x\cdot \frac{log_{4}\frac{7}{2}}{log_{4}14\cdot log_{4}49}} ≤ log_{4}49[/m]
[m]\frac{log_{4}(2-x)\cdot log_{4}49 }{log_{4}x} ≤ log_{4}49[/m]
[m]\frac{log_{4}(2-x)}{log_{4}x} ≤ 1[/m]
[m]\frac{log_{4}(2-x)}{log_{4}x} -1≤ 0[/m]
[m]\frac{log_{4}(2-x)-log_{4}x}{log_{4}x} ≤ 0[/m]
Применяем [i]обобщенный[/i] [b]метод интервалов.[/b]
[m]log_{4}(2-x)-log_{4}x=0[/m] ⇒ [m]log_{4}(2-x)=log_{4}x[/m] ⇒ [m] 2-x=x[/m]
[m]x=1[/m]
[m]log_{4}x=0 [/m]⇒ [m]x=1[/m]
(0) __+___ (1) ___+___ (2)
О т в е т. (0;1)U(1;2)